Memory and myths of the Norman Conquest - Brownlie, Siobhan (Medievalism (Series), 2013)
The Norman Conquest is one of the most significant events in British history - but how is it actually remembered and perceived today? This book offers a study of contemporary British memory of the Norman Conquest, focussing on shared knowledge, attitudes and beliefs. A major source of evidence for its findings are references to the Norman Conquest in contemporary British newspaper articles. A second important source of information is a quantitative survey for which a representative sample of 2000 UK residents was questioned. These sources are supplemented by the study of contemporary books and.